Math Proofs
Math Proofs
Math Proofs
Homework 5:
Theorem 1. Let a, b, and c be integers, where a and b are not both zero, and c is not zero. Then
gcd(ac, bc) = c · gcd(a, b).
Proof: [Note: As stated, this theorem is not true! If c < 0 it is not possible for gcd(ac, bc) = c · gcd(a, b)
because a greatest common divisor is always positive. I will give a proof that assumes that c > 0.]
Let d = gcd(a, b) and e = gcd(ac, bc). Since d | a and d | b, it follows easily that dc | ac and dc | bc. So,
dc is a common divisor of ac and bc. Since e is the greatest common divisor, we must have dc ≤ e.
We know d can be written as d = ak + b` for some integers k and `, and multiplying both sided by c
gives dc = ack + bc`. We also know that e is the smallest positive integer that can be written in the form
aci + bcj for integers i and j. Since dc can be written in that form, we must have dc ≥ e.
Since dc ≤ e and dc ≥ e, it follows that e = dc, as we wanted to show.
Theorem 2. Let a, b, c ∈ N, If a does not divide bc, then a does not divide b.
Proof: We prove the contrapositive: If a | b then a | bc. This is a theorem that we have previously
proved. [In fact, a | b means b = ka for some integer k. Then bc = bka = a(bk), which means that a | bc.]
Theorem 5. For any real number x, one of the numbers x and x − π is irrational.
Proof: Suppose, for the sake of contradiction, that both x and x − π are rational. Since the negative
of a rational number is rational, π − x is also rational. By the previous theorem, x + (π − x) is rational,
because it is the sum of two rational numbers. But x + (π − x) is π, which we know to be irrational. This
contradiction proves that at least one of x and π − x must be irrational.
Homework 6:
2. Prove using the contrapositive method: If the product of two integers is odd, then both of the numbers
are odd.
Proof: We prove the contrapositive: If it is not the case that both integers are odd, then the product of
the two numbers is not odd.
Let a and b be two integers that are not both odd. Then at least one of the integers is even. Say, without
loss of generality, that a is even. Then a = 2k for some integer k, and ab = 2kb. This shows that ab is even.
That is, ab is not odd.
3. Prove using proof by contradiction: If a is a rational number and b is an irrational number, then a + b is
an irrational number.
Proof: Assume, for the sake of contradiction, that a + b is rational. Since a is rational, −a is also
rational [since − pq = −p
q ]. We have previously proved that the sum of two rational numbers is rational. So
(a + b) + (−a) is rational. But (a + b) + (−a) = b, and b is irrational, not rational. This contradiction shows
that a + b cannot be rational.
4. Prove using the contrapositive method: If n is an integer and n ≡ 2 (mod 3), then n is not a square.
(Saying that n is not a square means that there is no integer a such that n = a2 .)
Proof: We prove the contrapositive: If n is a square, then n 6≡ 2 (mod 3). Let n be an integer that is
a square, and let a ∈ Z such that n = a2 . We need to show that a2 6≡ 2 (mod 3). Since every integer is
congruent to exactly one of 0, 1, or 2 (mod 3), we can show that for any integer a, either a2 ≡ 0 (mod 3) or
a2 ≡ 1 (mod 3). We use a proof by cases. Using the Division Algorithm, we can write a = 3q + r where q
and r are integers and r is 0, 1, or 2.
In the case a = 3q + 0, we have that a2 = (3q)2 = 3 · 3q 2 . This means 3 | a2 , and a2 ≡ 0 (mod 3).
In the case a = 3q + 1, we have that a2 = (3q + 1)2 = 9q 2 + 6q + 1 = 3 · (3q 2 + 2q) + 1. This means
3 | (a2 − 1), and a2 ≡ 1 (mod 3).
In the case a = 3q + 2, we have that a2 = (3q + 2)2 = 9q 2 + 12q + 4 = 3 · (3q 2 + 4q + 1) + 1. This means
3 | (a2 − 1), and a2 ≡ 1 (mod 3).
So, in any case, one of a2 ≡ 0 (mod 3) or a2 ≡ 1 (mod 3) is true, as we wanted to show.
We show that the left-hand side of this equation is an odd number, and so cannot be equal to zero. This
contradiction will complete the proof.
To show p3 + pq 2 + q 3 is odd, we use a proof by cases. Since we know that p and q are not both even,
the cases are: both p and q are odd, p is odd and q is even, or p is even and q is odd.
In the case where p and q are both odd, then, because the product of odd numbers is odd, we know that
p3 , pq 2 , and q 3 are all odd. Since the sum of odd numbers is odd, it follows that p3 + pq 2 + q 3 is odd.
In the case where p is odd and q is even, we have that p3 is odd and pq 2 + q 3 = q(pq + q 2 ) is even. Since
the sum of an odd number and an even number is odd, p3 + pq 2 + q 3 is odd.
Finally, in the case where p is even and q is odd, we have that q 3 is odd and p3 + pq 2 = p(p2 + q 2 ) is
even. Since the sum of an odd number and an even number is odd, p3 + pq 2 + q 3 is odd.